CDK1 Is a Synthetic Lethal Target for KRAS Mutant Tumours. - Sara Costa-Cabral; Rachel Brough; Asha Konde; Marieke Aarts; James Campbell; Eliana Marinari; Jenna Riffell; Alberto Bardelli; Christopher Torrance; Christopher J Lord; Alan Ashworth (PLoS ONE, 2016)
Activating KRAS mutations are found in approximately 20% of human cancers but no RAS-directed therapies are currently available. Here we describe a novel, robust, KRAS synthetic lethal interaction with the cyclin dependent kinase, CDK1. This was discovered using parallel siRNA screens in KRAS mutant and wild type colorectal isogenic tumour cells and subsequently validated in a genetically diverse panel of 26 colorectal and pancreatic tumour cell models. This established that the KRAS/CDK1 synthetic lethality applies in tumour cells with either amino acid position 12 (p.G12V, pG12D, p.G12S) or amino acid position 13 (p.G13D) KRAS mutations and can also be replicated in vivo in a xenograft model using a small molecule CDK1 inhibitor. Mechanistically, CDK1 inhibition caused a reduction in the S-phase fraction of KRAS mutant cells, an effect also characterised by modulation of Rb, a master control of the G1/S checkpoint. Taken together, these observations suggest that the KRAS/CDK1 interaction is a robust synthetic lethal effect worthy of further investigation.